Development of new deliquoring method with bypass discharge mechanism in centrifuge - Nishimura, Hitoshi; Iwasaki, Tomohiro; Jami, Mohammed Saedi; Iwata, Masashi (2017)
INTRODUCTION Centrifugal deliquoring is used in many industrial processes (e.g., chemical, food, pharmaceutical and biotechnological processes). A high driving force for solid liquid separation by a centrifuge can easily be obtained, resulting in a short processing time. However, during deliquoring of a slurry with poor filterability by a centrifuge, cake with poor permeability forms near the filter medium. Thus, such a slurry cannot be separated effectively by a conventional centrifuge. A new deliquoring method is developed to solve this problem. A schematic drawing of the new method is shown in Fig. 1. In this method, a new filter medium is placed parallel to the centrifugal force. In this study, the effect of the new filter medium on the consolidation process is evaluated, and an analytical method for deliqouring process using the new filter medium is proposed.